THEORY + PRACTICE. - Paglen, Trevor; Appelbaum, Jacob (Bomb (0743-3204))
The article focuses on a videoconference between artist and photographer Trevor Paglen and collaborator, activist, computer security expert and hacker Jacob Appelbaum as part of a symposium by the NYC Goethe-Institut. Topics discussed include Paglen and Appelbaum's advocacy for the global peer-to-peer anonymity network Tor, the Internet as a tool of mass surveillance and totalitarianism, and the Autonomy Cube which aims to find an alternative to the Internet network.